2018
DOI: 10.1016/j.niox.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Development of a portable mini-generator to safely produce nitric oxide for the treatment of infants with pulmonary hypertension

Abstract: The mini-NO generator safely produced therapeutic levels of NO from air. The mini-NO generator is an effective and economical approach to producing NO for treating neonatal pulmonary hypertension and will increase the accessibility and therapeutic uses of life-saving NO therapy worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…To develop a lighter NO generator for potential portable, outpatient use, we designed a miniaturized version of the prototypic NO generator, designated the ‘mini‐NO generator’ (Yu et al ., 2018). The mini‐NO generator weighs approximately 14 g and consists of two iridium electrodes within a ceramic insulator surrounded by a 3 mm aluminium housing.…”
Section: Generating No From Air Using Pulsed Electrical Dischargesmentioning
confidence: 99%
See 1 more Smart Citation
“…To develop a lighter NO generator for potential portable, outpatient use, we designed a miniaturized version of the prototypic NO generator, designated the ‘mini‐NO generator’ (Yu et al ., 2018). The mini‐NO generator weighs approximately 14 g and consists of two iridium electrodes within a ceramic insulator surrounded by a 3 mm aluminium housing.…”
Section: Generating No From Air Using Pulsed Electrical Dischargesmentioning
confidence: 99%
“…We showed that a small amount of Ca(OH) 2 scavenger (0.8 g) was sufficient to remove potentially toxic gases. Scanning electron microscopy and energy‐disperse X‐ray spectroscopy measurements demonstrated that a single HEPA filter was sufficient to remove all trace metal particles produced during prolonged NO generation (Yu et al ., 2018). An airflow of 70 mL·min −1 was sufficient to maintain the housing of the mini‐NO device at an acceptable low temperature during prolonged NO generation.…”
Section: Generating No From Air Using Pulsed Electrical Dischargesmentioning
confidence: 99%
“…77 The system uses an antioxidant reactor scrubber that minimizes NO 2 . The AirNOvent (AIT Therapeutics) 78 and eNO (Third Pole Therapeutics) 79,80 are capable of generating INO from ambient air using an electrical discharge (plasma/iridium spark) to create NO 2 , which is converted to nitric oxide using a scrubber that requires daily changing. This on-demand system can produce concentrations of 1-400 ppm without the use of tanks.…”
Section: Ino Delivery Systemsmentioning
confidence: 99%
“…Also in development is a miniaturized system that electrically generates nitric oxide, which may make INO delivery in the home more accessible and be a more economical option for developing countries. 7 Undoubtedly, there are bench-to-bedside research opportunities for understanding how these devices will interact with various ventilators.…”
mentioning
confidence: 99%